Central venous catheter-related infection - Mer, Mervyn (My University, 2014)
Introduction and Background: Central venous catheters (CVCs) are extensively used worldwide. Mechanical, infectious and thrombotic complications are well described with their use and may be associated with prolonged hospitalisation, increased medical costs and mortality. CVCs account for an estimated 90% of all catheter-related bloodstream infections (CRBSI) and a host of risk factors for CVC-related infections have been documented. These include, most importantly, the duration of catheterisation. The duration of use of CVCs remains controversial and the length of time such devices can safely be left in place has not been fully and objectively addressed in the critically ill patient. Over the past few years, antimicrobial impregnated catheters have been introduced in an attempt to limit catheter-related infection (CRI) and increase the time that CVCs can safely be left in situ. Recent meta-analyses concluded that antimicrobial-impregnated CVCs appear to be effective in reducing CRI. Materials and Methods: This was a prospective randomised double-blind study performed in the adult multidisciplinary Intensive Care Unit (ICU) at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) over a four year period. The study entailed a comparison of standard triple-lumen versus antimicrobial impregnated CVCs on the rate of CRI. The aim was to determine whether the duration of catheter insertion time could safely be increased from the standard practice of seven days at the CMJAH adult multidisciplinary ICU to 14 days, to assess the influence of the antimicrobial impregnated catheter on the incidence of CRI, and to elucidate the epidemiology and risks of CRI. Results: One hundred and eighteen critically ill patients were included in the study which spanned 34 951.5 catheter hours (3.99 catheter years). Sixty-two patients received a standard triple-lumen catheter and 56, a chlorhexidine-silver sulfadiazine (CSS) impregnated triple-lumen catheter. The mean duration of placement for the full sample of 118 CVCs was 12.3 days (range, 1-14). No statistically significant difference in CRI rates between the two types of catheters could be demonstrated. The most common source of primary CRBSI was skin, followed by hub and infusate. The site of CVC insertion (internal jugular versus subclavian vein) and the use of parenteral nutrition were not noted to be risk factors for catheter infection. There was no clinical evidence of catheter-related thrombosis in either of the study groups. Conclusion: This study was unable to demonstrate that antimicrobial catheters provided any significant benefit over standard catheters, which it is felt, can safely be left in place for up to 14 days with appropriate infection control measures. The most common source of CRI was the skin. The administration of parenteral nutrition and the site of catheter insertion (internal jugular vein versus subclavian vein) were not noted to be risk factors for CRI. There was no clinical evidence of thrombotic complications in either of the study groups. This study offers direction for the use of CVCs in critically ill patients and addresses many of the controversies that exist.
Keywords: central venous catheters; infection; duration; thrombosis